Legal Protection for Misuse of Television Station Logo Without Permission in Tiktok Social Media - Rizka, Rizka; Azizah, Isnaini Dina (Universitas Semarang, 2024)
This writing aims to find out the form of legal protection against misuse of the logo without permission and to find out the legal consequences for content creators on TikTok social media who misuse the logo. This research can provide information to content creators and the public to protect logos and to find out the legal consequences for parties who misuse logos. In this writing, normative legal research methods are used. This article has a novelty, namely a more specific discussion of logo misuse in terms of Law No. 20 of 2016 and the consequences of misuse of logos on social media. The result of this writing is to find out the form of legal protection for the owner of the rights to the logo, if the logo owner experiences a loss caused by another party then the party who caused the loss can be given sanctions in accordance with Law No. 20 of 2016 and to find out the legal consequences for content creators who misuse the logo without permission on TikTok social media are subject to imprisonment and/or fines as regulated in Law No. 20 of 2016, and can also file a civil suit for compensation and/or to stop misuse of the logo. If the violation is committed on social media, you can be sentenced to imprisonment for a maximum of 4 years and/or a fine of a maximum of IDR. 750,000,000,- (seven hundred and fifty million rupiah) as regulated in article 45 paragraph 3 of the ITE Law.